Legal Protection for Victims of Domestic Violence (Study Decision Number 81/Pid.Sus/2023/PN Liw) - Baharudin Baharudin; Yulia Hesti; Fajaruddin Yusuf (CV. Rayyan Dwi Bharata, 2024)
Domestic Violence is defined as any act against an individual, especially women, resulting in physical, sexual, psychological suffering, or neglect, including threats of such acts, coercion, or unlawful deprivation of freedom within the household context. The issues addressed in this research are the obstacles in providing protection for victims of domestic violence based on decision number 81/Pid.Sus/2023/PN Liw, and the efforts to ensure legal protection for these victims according to the same decision. The research methodology utilizes a normative juridical approach, which involves examining applicable laws, and an empirical approach, which includes field observations and interviews to address the research problems. Based on the research findings, the obstacles in enforcing the law to protect victims include limited resources such as personnel and facilities. Additionally, victims often hesitate to report incidents due to a desire to maintain relationships with the perpetrators or due to shame related to family honor. Factors such as anxiety and difficulty in reporting incidents, even when they recur, contribute to the challenge. Issues like embarrassment, fear, and trauma hinder effective protection for victims. Protection efforts include police actions to ensure safety and escort victims to safer locations, coordination by the prosecution with police, witness and victim protection agencies, and health institutions to ensure victims receive protection and recovery support. Courts issue protection orders prohibiting perpetrators from approaching or contacting victims and may order separation of living arrangements as an additional protective measure. Recommendations from the author include: Enhancing cooperation among government agencies such as the police, prosecution, courts, health institutions, and witness and victim protection agencies. Good coordination will ensure victims receive comprehensive protection and support. There is a need to improve resources, including personnel, budgets, and facilities for relevant agencies to provide adequate protection for domestic violence victims. Adequate resources will enable maximal protection and support for victims. Law enforcement should broaden public awareness of domestic violence, challenge societal stigma, and emphasize the importance of reporting perpetrators. Victims require ongoing support, including counseling, rehabilitation, and social assistance. Relevant agencies should ensure victims have access to these services for physical and psychological recovery. Law enforcement should also work to enhance legal protection for domestic violence victims and address existing obstacles.